2013
DOI: 10.1080/02699931.2012.755119
|View full text |Cite
|
Sign up to set email alerts
|

Losing control, literally: Relations between anger control, trait anger, and motor control

Abstract: Self-control perspectives of multiple traits have been proposed, perhaps most particularly so in the anger realm. Four studies sought to examine potential relations between anger control, trait anger, and motor control. Across the four studies, individuals (total N=366) were asked to hold a joystick cursor on a spatial target as accurately and steadily as possible and two indices of motor control were quantified. Studies 1 and 2 found that higher levels of (trait) anger control were predictive of better motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
1
5
1
Order By: Relevance
“…Our finding that HTA and LTA individuals performed equally well on our task measuring inhibitory control was in contrast with previous studies that showed reduced hostility-primed inhibitory control in HTA individuals (Bresin and Robinson, 2013;Wilkowski and Robinson, 2008a), but in line with the study of Hull et al (2003) who found no relation between trait anger and inhibitory control. Interestingly, studies conducted with individuals high on trait aggressiveness, a concept distinct from but closely related to trait anger (Bettencourt et al, 2006;, have also shown mixed results (Denny and Siemer, 2012;Krämer et al, 2011;Pawliczek et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our finding that HTA and LTA individuals performed equally well on our task measuring inhibitory control was in contrast with previous studies that showed reduced hostility-primed inhibitory control in HTA individuals (Bresin and Robinson, 2013;Wilkowski and Robinson, 2008a), but in line with the study of Hull et al (2003) who found no relation between trait anger and inhibitory control. Interestingly, studies conducted with individuals high on trait aggressiveness, a concept distinct from but closely related to trait anger (Bettencourt et al, 2006;, have also shown mixed results (Denny and Siemer, 2012;Krämer et al, 2011;Pawliczek et al, 2013).…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, studies conducted with individuals high on trait aggressiveness, a concept distinct from but closely related to trait anger (Bettencourt et al, 2006;, have also shown mixed results (Denny and Siemer, 2012;Krämer et al, 2011;Pawliczek et al, 2013). One explanation could be that the anger-related pictures used in the current study were not salient enough to elicit sufficient recruitment of effortful resources in contrast to previous studies (Bresin and Robinson, 2013;Wilkowski and Robinson, 2008a). For instance, one difference between our study and these previous studies is that we used anger-related pictures instead of anger-related words to prime anger.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Such ambiguities can be bypassed with a tighter temporal frame because, in momentary terms, no one is fully in control of their behavior (Slifkin & Newell, 1998). One can study micromomentary efforts at control to gain insights into vagaries in self-control processes as well as the individual differences that seem to matter in their operation (Bresin & Robinson, 2013; Klein & Robinson, 2019). This approach should “work,” according to cybernetic theory, because the success of any large-scale behavior (e.g., studying, having an effective conversation) is likely to depend on more momentary operations, like those involved in motor control (Carver & Scheier, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The motor control paradigm was a dense, data-rich one due to the use of multiple trials (70) and many samples per trial (40). In the context of this platform, we wanted good (.90) power to detect correlation-related relationships between personality and performance in the .30 range (.05 α, two-tailed), following precedent (Bresin & Robinson, 2013; Klein & Robinson, 2019). G*Power software (Faul et al, 2009) informed us that a sample of 88 participants would give us this level of power, both with respect to main effects and interactions, and we ran the study for long enough to exceed this number.…”
Section: Methodsmentioning
confidence: 99%